2012
DOI: 10.5539/ies.v5n5p43
|View full text |Cite
|
Sign up to set email alerts
|

Employability Skills Assessment Tool Development

Abstract: Research nationally and internationally found that technical graduates are lacking in employability skills. As employability skills are crucial in outcome-based education, the main goal of this research is to develop an Employability Skill Assessment Tool to help students and lecturers produce competent graduates in employability skills needed by the industry. The employability skill Assessment Tool were developed using the Kepner-Tregoe (K-T) method. Samples were 107 employers from five types of Malaysian man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…From the perspective of an employer, trainings are provided to staff in order for staff to be a global competitive player, and be ahead of competitors. With a borderless world in the IT industry, staff must be value added with necessary technical and non-technical expertise (Rasul, Rauf, Mansor & Puvanasvaran, 2012). Manager A mentioned, "…We have now, you know competitors, so we need to make sure that our talent is valued and the investors are willing to come because we have competent talents…"…”
Section: Theme 1: Competitive Global Market Playermentioning
confidence: 99%
“…From the perspective of an employer, trainings are provided to staff in order for staff to be a global competitive player, and be ahead of competitors. With a borderless world in the IT industry, staff must be value added with necessary technical and non-technical expertise (Rasul, Rauf, Mansor & Puvanasvaran, 2012). Manager A mentioned, "…We have now, you know competitors, so we need to make sure that our talent is valued and the investors are willing to come because we have competent talents…"…”
Section: Theme 1: Competitive Global Market Playermentioning
confidence: 99%
“…As job market needs vary among different regions of the world, the competencies and skills that are required to maintain employability vary as well [19]. Further, research in various regions of the world has indicated that numerous graduates lack the employability skills that are required by employers [30]. In the last few decades, however, the demand for highly technical and professional skills has increased throughout the world [22].…”
Section: Employability Skills Among Various Regions Of the Worldmentioning
confidence: 99%
“…There is a growing concern that university graduates lack employability skills around the world (Australian Department of Education, 2006;Confederation of British Industry;Rasul, Rauf, Mansor, & Puvanasvaran, 2012;UNESCO, 2012). In Japan, the Ministry of Economy, Trade, and Industry (METI, 2014) introduced the concept of syakaijin kisoryoku (fundamental competencies for working persons as translated by METI: See Appendix A) in 2006 and the Ministry of Education, Culture, Sports, Science, and Technology (MEXT, 2008) introduced the concept of gakushiryoku (competences expected of university graduates: See Appendix B) in 2008 in an attempt to help develop students' employability skills.…”
Section: Introductionmentioning
confidence: 99%